Tingkat Kepuasan Pasien Swamedikasi Terhadap Pelayanan Informasi Obat di Apotek Pesisir Surabaya Timur - Oki Nugraha Putra; Angelica Kresnamurti; Akalili Yunita (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Pharmacy is a facility for pharmaceutical services conducted by pharmacists. One of pharmaceuticalservices performed at a pharmacy is swamedication services. The purpose of this study was to determine thelevel of satisfaction of swamedication patients in drug information services in several pharmacies in the EastSurabaya Coastal Area, based on fi ve dimensions of service quality, namely reliability, responsiveness, assurance, empathy and tangibles. This cross sectional study using a validated questionnaire instrument. The research sample is swamedication patients who meet the inclusion criteria. Swamedication patients were selected nonrandomly by consecutive sampling method. Data retrieval was carried out in October-December 2018. Data from the fi ve dimensions of service quality were analyzed by the SERVQUAL method. There were 100 patients who performed swamedication services that met the inclusion criteria. The results showed that the average gap between expectation and performance is -0.36 with the largest gap value indicated on the reliability dimension of -0.51. At overall satisfaction level, the results are 89%. The conclusion is that the level of expectations of swamedication patients is higher than the level of performance of drug information services provided by the pharmacy with a good level of patient satisfaction.